Where do journalists go after newsroom job cuts?. (2nd January 2016) - O'Donnell, Penny; Zion, Lawrie; Sherwood, Merryn
Abstract : This article explores the aftermath of job loss in journalism in 2012, a year of dramatic press industry restructuring in Australia. It reports the findings of a pilot survey of 95 Australian redundant journalists, undertaken as part of the New Beats project, a five-year, university–industry investigation of what happens to journalists, and journalism, after job loss. Three related questions drive the analysis: Where do journalists go after job cuts? How do they make sense of job loss? What happens to professional identity? In contrast to a recent study of journalists laid off from the British press, and the literature on the aftermath of job loss for older professionals, this research finds that, in practical terms, the Australian journalists had relatively better than expected post-job loss experiences. All but two of the redundant journalists seeking re-employment found some form of work within one year, and, thanks to union-enforced redundancy agreements, most left newsrooms with severance payments that cushioned the financial impact of unemployment. Yet, the majority did not resume their full-time careers in journalism, and many were emotionally traumatised not only by job loss but also career change. The article argues a sense of leaving a newspaper industry in seemingly terminal decline amplified feelings of anger and anxiety about both the future of journalism work, and lost professional identity, prompting many to leave the profession intentionally and seek jobs elsewhere.